Telaah Yuridis Kesiapan Unit Usaha Syariah untuk Dipisahkan dari Bank Konvensional(Studi Kasus Di Bank Syariah Bukopin Dan Bni Syariah) - Ahzar, Rizki Maulana; , Wardah Yuspin, S.H.,M.Kn.,Ph.D (2017)
Bank has developed its system from conventional to syariah which is based on Islamic system.Syariah business unit is a part of a conventional bank which runs business activity based on Islamic system. A Spin off of this system is regulated in 68th article verse (1) UU No. 21 year 2008. Spin off must be done by the conventional bank which has syariah unit whose asset is 50% or more on its conventional bank. Spin off also must be done when a syariah bank has been operating for 15 years. This research aims to analyze about the readiness of Syariah Bukopin and BNI Syariah Bank before spin off, their performance after spin off and the impact of the spin off. The type of this research is juridical-empirical system which applied qualitative methodology. The location of this research is in Syariah Bukopin Bank Melawai, South Jakarta and BNI Syariah Bank Surakarta. This research results the information of the readiness, performance and the impact of Syariah Business Unit spin off. Keywords : Spin off, Syariah Business Unit, Syariah Public Bank